Embroidering Narratives of Resistance: Practices and Experiences of Older Female Activists (Polis (Santiago), 2021)
Conventional models of old age place older women in worse conditions than men, describing them as a homogeneous group and neglecting their potential and resources. This paper addresses the experiences and practices of resistance that older women activists from the group Bordadoras por la Memoria de Chile (Embroiderers for Memory of Chile) deploy in their daily lives in the context of the Covid19 pandemic. In affinity with feminist gerontology and situated knowledge, the use of the methodology of group narrative productions allowed us to delve deeper into the strategies that women activists employ to contest conventional old age. The results show that their experience of ageing through political action allows them to resist health confinement, to innovate in their routines and forms of communication, and to create new strategies for problem solving. From this place, they question the mandates of normativity in old age and reflexively criticise public and institutional action aimed at the elderly in Chile. It is concluded that the knowledge produced by women tensions and disputes positions, transgressing representations of old age that marginalizes them, visualizing their agency and social contributions.
Keywords: Feminist gerontology; old age; agency; narrative productions.